Preparation of Ag@AgCl-doped TiO2/sepiolite and its photocatalytic mechanism under visible light - Liu, Shaomin; Zhu, D.; Zhu, J.; Yang, Q.; Wu, H. (2017)
© 2017. A cube-like Ag@AgCl-doped TiO 2 /sepiolite (denoted Ag@AgCl-TiO 2 /sepiolite) was successfully synthesized via a novel method. X-ray diffraction, scanning electron microscopy, energy dispersion X-ray fluorescence, X-ray photoelectron spectroscopy, Fourier transform infrared spectroscopy, and diffuse reflectance ultraviolet-visible spectroscopy were performed to determine the structure and physicochemical properties of Ag@AgCl-TiO 2 /sepiolite. SEM micrographs revealed that Ag@AgCl nanoparticles and TiO 2 film are well deposited on the surface of tube-like sepiolite. As a result, Ag@AgCl-TiO 2 /sepiolite exhibits a red shift relative to TiO 2 /sepiolite. Photocatalytic experiments demonstrated that the dosage of catalysts plays an important role during photocatalysis. The photoelectrochemical activities of Ag@AgCl-TiO 2 /sepiolite and TiO 2 /sepiolite were also investigated. Photocurrent responses confirmed that the ability of Ag@AgCl-TiO 2 /sepiolite to separate photo-generated electron-hole pairs is stronger than that of TiO 2 /sepiolite. Methylene Blue degradation is also improved under alkaline conditions and visible light irradiation because more OH is produced by visible light excitation. This excellent catalytic ability is mainly attributed to the formed Ag nanoparticles and the Schottky barrier at the Ag/TiO 2 interface. Active species analysis indicated that O 2 - and h + are implicated as active species in photocatalysis. Therefore, catalysts are excited to produce abundant electron-hole pairs after they absorb photons in photocatalysis.